2004
DOI: 10.1086/420743
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome

Abstract: The first cases of severe acute respiratory syndrome (SARS) occurred in China in November 2002. The agent causing this illness has been identified as a novel coronavirus, SARS-coronavirus. Since its introduction <1 year ago, this virus has infected 8098 people in 26 countries, killing 774 of them. We present an overview of the epidemiology, clinical presentation, diagnosis, and treatment of SARS based on the current state of knowledge derived from published studies and our own personal experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
131
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(139 citation statements)
references
References 46 publications
1
131
0
7
Order By: Relevance
“…The SARS epidemic was contained at 8098 cases with 774 deaths. In addition to the human misery caused, there were direct economic consequences for those countries most affected (Christian et al, 2004).The causative agent of SARS was identified as a new type of coronavirus, the SARS coronavirus (SARS-CoV). SARS-CoV is an enveloped virus with a positive-sense, single-stranded RNA genome of 29 727 nt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS epidemic was contained at 8098 cases with 774 deaths. In addition to the human misery caused, there were direct economic consequences for those countries most affected (Christian et al, 2004).The causative agent of SARS was identified as a new type of coronavirus, the SARS coronavirus (SARS-CoV). SARS-CoV is an enveloped virus with a positive-sense, single-stranded RNA genome of 29 727 nt.…”
mentioning
confidence: 99%
“…The SARS epidemic was contained at 8098 cases with 774 deaths. In addition to the human misery caused, there were direct economic consequences for those countries most affected (Christian et al, 2004).…”
mentioning
confidence: 99%
“…The high mortality rate of the disease and its easy transmission to health care workers characterize its clinical importance (1,10,12,13). The clinical manifestations, laboratory findings, radiologic presentations, and outcomes of SARS for patients have been well described (3,9,12). Previous reports also found that the specific antibody to SARS-associated coronavirus (SARS-CoV) appears as early as 9 days after the disease onset and that a high level of antibody could last for 1 to 2 months after the onset of SARS (2,5,9).…”
mentioning
confidence: 99%
“…zespół chorobowy stwierdzono w Chinach w 2003 r. Kolejne przypadki SARS wystąpiły w Chinach oraz 33 innych krajach, co powoduje, że chorobę tę uznano za szczególnie ważną zoonozę. Wirus ten rozprzestrzeniając się na całym świecie, był przyczyną ponad 8000 przypadków zachorowań, w tym 700 przypadków śmiertelnych (17,55,83). SARS-CoV w większości przypadków ewoluował, a prawdopodobnie pierwotnym źródłem była populacja nietoperzy z rodziny podkowcowatych (Rhinolophidae), z gatunku podkowiec chiński (Rhinolophus sinicus) oraz inne gatunki nietoperzy uznawane za naturalny rezerwuar tych drobnoustrojów (57).…”
Section: Artykuł Przeglądowy Reviewunclassified